Modulus of Convexity, the Coeffcient R(1,X), and Normal Structure in Banach Spaces - Hongwei Jiao; Yunrui Guo; Fenghui Wang (Abstract and Applied Analysis, 2008)
Let δX(ϵ) and R(1,X) be the modulus of convexity and the Domínguez-Benavides coefficient, respectively. According to these two geometric parameters, we obtain a sufficient condition for normal structure, that is, a Banach space X has normal structure if 2δX(1+ϵ)>max{(R(1,x)-1)ϵ,1-(1-ϵ/R(1,X)-1)} for some ϵ∈[0,1] which generalizes the known result by Gao and Prus.